Evaluation of the Toddler Family Development Activity Group - Selvie Nofriani Tansile; Finta Amalinda (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2023)
The government's effort to overcome growth and development problems in toddlers is to integrate activities for the Toddler Family Development (BKB), Integrated Service Post (Posyandu) and Early Childhood Education (PAUD). The condition of the activities of BKB, Posyandu and PAUD so far seems to run independently so that there is a need for policies to synergize them so that the educational goals of